EFFORTS TO IMPROVE WRITTEN COMMUNICATION SKILLS AND STUDENTS' SCIENTIFIC ATTITUDES BY USING THE DISCOVERY LEARNING LEARNING MODEL AT AL-HASAN MADANI ISLAMIC BOARDING SCHOOL RIAU - Sara Rahmawati; Fakhruddin Z; Dedi Irawan (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
Observation results at the Al-Hasan Madani Islamic Boarding School in Riau showed low communication skills, as seen from the lack of active participation in group discussions, difficulty conveying logical arguments, and low courage to ask questions. The results of the needs analysis of 25 students revealed that students still have suboptimal written communication skills, with a percentage of 48%. In addition, scientific attitudes such as curiosity and reflection skills have not developed optimally, with a percentage of 44% being in the low category. This condition is also supported by the learning model that is still teacher-centered. The purpose of this study is to observe the involvement/activities of educators and students during learning activities and to find effective ways in learning by using the discovery learning model to improve written communication skills and scientific attitudes of students at the Al-Hasan Madani Islamic Boarding School in Riau. The type of research used is Classroom Action Research (CAR) with 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class X B. This study conducted at an Al-Hasan Madani Islamic Boarding School in Riau. There were 25 students of class X B. The dependent variable in this study was students' written communication skills and scientific attitudes. While the independent variable in this study was the discovery learning model. Data collection methods included observation sheets of educator and student activities, written communication skills tests, student scientific attitude questionnaires, and documentation. Based on the results of this study, it can be concluded that the application of the discovery learning model at the Al-Hasan Madani Islamic Boarding School in Riau is considered effective, and with increased educator and student activities, it can improve students' written communication skills and scientific attitudes. This increase occurred gradually, starting from the initial data at the pre-cycle stage, cycle I, to cycle II. The percentage of educator activity obtained in the implementation of Cycle I learning was in the good category and the implementation of Cycle II learning was in the very good category. While the percentage of students in the implementation of Cycle I learning was in the good category and the implementation of Cycle II learning was in the very good category.